Spontaneous transitions between amoeboid and keratocyte-like modes of migration - Moldenhawer, Ted; Moreno, Eduardo; Schindler, Daniel; Flemming, Sven; Holschneider, Matthias; Huisinga, Wilhelm; Alonso, Sergio; Beta, Carsten (Frontiers in Cell and Developmental Biology, 2022)
The motility of adherent eukaryotic cells is driven by coherent patterns of activity in the actin cytoskeleton. Despite the common force-generating actin machinery, different cell types often show diverse modes of locomotion that differ in their shape dynamics, speed, and persistence of motion. Recently, experiments with the model organism Dictyostelium discoideum have revealed that different motility modes can be induced in the same cell type, depending on genetic modifications, developmental conditions, and synthetic changes of intracellular signaling. Here, we report experimental evidence that switches between two distinct migratory modes, the amoeboid and fan-shaped type of locomotion, can spontaneously occur within the same cell. We observed repeated and reversible switchings between the two modes of locomotion, suggesting that both migratory modes are stable coexisting behavioral states with spontaneous noise-induced transitions occurring between them. Furthermore, we adapted an established motility model that combines a reaction-diffusion system for the intracellular dynamics with a dynamic phase field to account for our experimental findings.